2017
DOI: 10.18632/oncotarget.23393
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics reveals altered biosynthetic pathways of glycerophospholipids and cell signaling as biomarkers of the polycystic ovary syndrome

Abstract: PurposeIn this work, a non-targeted approach was used to unravel changes in the plasma lipidome of PCOS patients. The aim is to offer new insights in PCOS patients strictly selected in order to avoid confounding factors such as dyslipemia, obesity, altered glucose/insulin metabolism, cardiovascular disease, or cancer.ResultsMultivariate statistics revealed a specific lipidomic signature for PCOS patients without associated pathologies. This signature implies changes, mainly by down-regulation, in glycerolipid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 74 publications
4
20
2
Order By: Relevance
“…The expanding development of omics approaches has allowed a wider view of the molecular mechanisms underlying human pathology. Indeed, we have recently confirmed a specific plasma lipidomic signature in women with PCOS with respect to healthy individuals 21 . This signature implies changes in the metabolism of glycerolipids, glycerophospholipids and sphingolipids, pointing to changes in the glycerophospholipid biosynthetic pathway and cell signalling.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…The expanding development of omics approaches has allowed a wider view of the molecular mechanisms underlying human pathology. Indeed, we have recently confirmed a specific plasma lipidomic signature in women with PCOS with respect to healthy individuals 21 . This signature implies changes in the metabolism of glycerolipids, glycerophospholipids and sphingolipids, pointing to changes in the glycerophospholipid biosynthetic pathway and cell signalling.…”
Section: Introductionsupporting
confidence: 59%
“…In addition to hormonal derangements and altered glucose metabolism, PCOS has traditionally been linked with atherogenic dyslipidemia, a major determinant of cardiovascular diseases 20 . However, a recent study performed with PCOS patients without associated pathologies and presenting a non-pathogenic lipid profile (Total cholesterol, LDL-C, HDL-C and TG) describes the presence of a PCOS lipidomic fingerprint, in which glycerolipid, glycerophospholipid and sphingolipid metabolism is affected 21 , suggesting that these molecules are related to the physiopathology of PCOS and opening up new scenarios in the search for new drugs. Therefore, the lipid profile characterized by high triglycerides 22 , low HDL cholesterol and increased LDL cholesterol, which has been related to androgen excess 22,23 , is a classic profile linked to IR rather than PCOS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were then shaken vigorously for 2 min. Then methyl tert-butyl ether (MTBE) containing lipid standards 30 (isotopically labelled lipids) was added for external and internal standardization. Samples were then immersed in a water bath (ATU Ultrasonidos, Valencia, Spain) with an ultrasound frequency 40 kHz and power of 100 W, at 10 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it has been suggested that FAs are associated with the risk of a wide range of chronic diseases such as PCOS [12,13]. In this regard, trans-FA (TFA) and saturated FA (SFA) are reported to play significant roles in the development of several disorders through their stimulating action and n-3 polyunsaturated fatty acids (PUFA) contribute by their suppressive action [11,[13][14][15]. The increased amounts of linoleic acid (LA; C18:2 n-6) by 136% in the AT over the last half century in the United States [16], and the increase in the dietary n-6:n-3 FA ratio from 1:1 to 20:1 [17], point to their possible roles in chronic diseases such as PCOS.…”
Section: Introductionmentioning
confidence: 99%